Electrophysical properties of singlecrystal silicon sequentially doped with sulfur and zinc impurity atoms (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The paper studies electro physical properties of single crystal silicon after gradual (firstsulfur, afterwards -zinc) diffusion of impurity atoms of sulfur and zinc. The authors investigated how the Si2ZnS -structured binary compounds form in the crystal lattice of silicon and also studied the physical mechanisms of how additional thermal treatment might influence the process of formation of clusters.